Клеточные и молекулярные основы заживления ран - Макеева, Л. В.; Славчева, О. С.; Сулаева, О. Н.; Завгородняя, М. И.; Makeieva, L. V.; Slavcheva, O. S.; Sulaieva, O. N.; Zavgorodniaia, M. I.; Макєєва, Людмила Валеріївна; Славчева, Оксана Сергіївна; Сулаєва, Оксана Миколаївна; Завгородня, Марія Ігорівна (My University, 2016)
Одной из актуальных проблем медицины является нарушение заживления ран. Репарация кожной раны - многофазный процесс, включающий взаимодействие различных клеток, факторов роста и цитокинов, и других сигнальных молекул, направленный на закрытие дефекта кожи и, как результат, восстановление целостности покровов тела. Целью данной работы является анализ современных данных о клеточных детерминантах и молекулярных механизмах течения раневого процесса. Помимо обсуждения механизмов смены клеточных популяций, авторы затрагивают вопросы возможности прогнозирования и управления процессом заживления кожных ран, новые стратегические направления лечения длительно незаживающих ран в рамках трансляционной медицины. The skin is the biggest organ of human body plays the crucial role in protection and defence. Any kind of the skin injury leads to functional imbalance, whereas severe damage can be associated with human disability or even death. At the same time, the skin injury initiates the mechanisms of curbing damage and subsequently inducing repair. Repair of the skin wounds is a complex multiphase process that comprises the dynamic series of overlapping phases and involves numerous cell subsets, inflammatory mediators, cytokines, chemokines, growth factors, proteolytic enzymes and other signal molecules aimed at the closure of the skin defect and, as a result, the restoration of the integrity of the integument. The process of wound healing goes through several phases: inflammation, proliferation and remodeling. These phases are orchestrated by the interplay of the cells participating in each phase and molecules produced by these cells. Due to the growing body of scientific research, plenty of information about the cellular and molecular regularities of the healing process is available. However this does not reduce the number of patients with delayed healing or non-healing chronic wounds. That is why wound healing violation is still the actual problem of current medicine. The aim of this work was to assess the current data concerning the cellular determinants, and molecular mechanisms of the wound healing. In addition to discussing the mechanisms of the cell populations’ exchange, the authors address questions of the ability to predict and manage the wound healing. The new strategies, including biotechnologies and cellular technologies in particular are discussed. Further investigation of the kinetics of different cell lines will allow detailing the role and mechanisms of different intercellular cooperation that is a prerequisite for the development of a new process of wound management strategy.
Cellular and molecular basics of the wound healing
Клітинні та молекулярні основи загоєння ран
Keywords: заживление ран; воспаление; репарация; ремоделирование кожи